Effects of physical exercise on markers of inflammation in breast cancer patients during adjuvant chemotherapy - Vulpen, Jonna K. van; Schmidt, Martina; Velthuis, Miranda J.; Wiskemann, Joachim; Schneeweiss, Andreas; Vermeulen, Roel C. H.; Habermann, Nina; Ulrich, Cornelia; Peeters, Petra H. M.; van der Wall, Elsken; May, Anne M.; Steindorf, Karen (Breast cancer research and treatment, 2018)
Exercise has been shown to reduce fatigue during cancer treatment. Hypothesized mechanisms include inflammatory pathways. Therefore, we investigated effects of exercise on markers of inflammation in breast cancer patients during adjuvant chemotherapy.